Ictal/postictal SPECT in the pre-surgical localisation of complex partial seizures. - Duncan, R (1993)
Single photon emission computed tomography (SPECT) used in conjunction with HM-PAO (Ceretec-Amersham International) was used to image regional cerebral blood flow (rCBF) in 28 patients with medically intractable complex partial seizures during or soon after a seizure, and interictally. Changes from interictal rCBF were seen in 26/28 (93%) patients. The main findings were; 1) During the seizure--hyperperfusion of the whole temporal lobe; 2) Up to 2m postically--hyperperfusion of the hippocampus with hypoperfusion of lateral temporal structures; 3) From 2-15m postically--hypoperfusion of the whole temporal lobe. When compared with EEG and MRI data, correct localisation to one temporal lobe was obtained in 23 patients. In one further patient bilateral temporal foci, and in a further two patients frontal foci, were correctly identified. There were no disagreements between EEG and SPECT localisation. Temporal lobe surgery was successful (by the criterion of at least 90% reduction in seizure frequency) in all but one of the 23 patients operated on. It is concluded that ictal/postictal SPECT is a reliable technique for the presurgical localisation of complex partial seizures. The data indicate a likely sequence of changes in rCBF during and after complex partial seizures of temporal lobe origin.